2001
DOI: 10.1021/jf0012493
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Enzyme Immunoassay for the Analysis of Carbaryl in Fruits and Vegetables without Sample Cleanup

Abstract: The N-methylcarbamate pesticide carbaryl is one of the most important insecticides used worldwide. In the present work, the validation of a monoclonal antibody-based enzyme immunoassay (ELISA) for the determination of this compound in fruits and vegetables is described. The immunoassay is a competitive heterologous ELISA in the antibody-coated format, with an I(50) value for standards in buffer of 101.0 +/- 26.9 ng/L and with a dynamic range between 31.6 and 364.0 ng/L. For recovery studies, peppers, cucumbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 12 publications
1
7
0
1
Order By: Relevance
“…Although fundamentally, the ELISA results were nearly equal to the chromatographic results, or tended to somewhat overestimate theoretical values except for some imidacloprid results, when considering average recovery rates as a whole (Fig. 9), the evaluated ELISAs showed tolerable agreement with the chromatographic methods for the three pesticides, and it can be concluded that all evaluated ELISAs are practical analytical techniques that can be used as quantitative screening methods to detect pesticides in crop samples, as described in several related reports 1,8,19,28 .…”
Section: Reliability Of Elisa and Comparison Between Elisa And Convensupporting
confidence: 54%
“…Although fundamentally, the ELISA results were nearly equal to the chromatographic results, or tended to somewhat overestimate theoretical values except for some imidacloprid results, when considering average recovery rates as a whole (Fig. 9), the evaluated ELISAs showed tolerable agreement with the chromatographic methods for the three pesticides, and it can be concluded that all evaluated ELISAs are practical analytical techniques that can be used as quantitative screening methods to detect pesticides in crop samples, as described in several related reports 1,8,19,28 .…”
Section: Reliability Of Elisa and Comparison Between Elisa And Convensupporting
confidence: 54%
“…An example for the advantage of immunoassays in this field is the monitoring of botulinum toxin in food, previously studied with a mouse bioassay, which can now be detected with a lateral flow device as an alternative [197]. Further examples of surveying for infectious agents, residues and contaminants are: -pathogenic microorganisms on food [198] -Staphylococcal enterotoxin B in milk [199] -pesticides in fruits [200] and rice [201] -human exposure to pyrethroid pesticides [202] -melamine in milk [203] -antibiotics in milk [204] -wheat proteins in milk powder [205] Brought to you by | University of Kent Authenticated Download Date | 12/14/17 7:10 PM…”
Section: Markers In Food Hygienementioning
confidence: 99%
“…An example for the advantage of immunoassays in this field is the monitoring of botulinum toxin in food, previously studied with a mouse bioassay, which can now be detected with a lateral flow device as an alternative [197]. Further examples of surveying for infectious agents, residues and contaminants are: -pathogenic microorganisms on food [198] -Staphylococcal enterotoxin B in milk [199] -pesticides in fruits [200] and rice [201] -human exposure to pyrethroid pesticides [202] -melamine in milk [203] -antibiotics in milk [204] -wheat proteins in milk powder [205] …”
Section: Markers In Food Hygienementioning
confidence: 99%